Investigating photoluminescence properties of Eu3+ doped CaWO4 nanoparticles via Bi3+ amalgamation for w-LEDs application. (29th July 2022) - Singh, Maheshwary; Haq, Waseem Ul; Bishnoi, Swati; Singh, Bheeshma Pratap; Arya, Sandeep; Khosla, Ajit; Gupta, Vinay
ABSTRACT: Eu 3+ -doped CaWO4 nanophosphors were synthesised in series for different atomic wt% concentrations (0, 0.5, 1, 2, 5 and 10) of Bi 3+ by polyol method. Their structure and morphology were characterised using X-ray diffraction (XRD) and scanning electron microscopy (SEM). The photoluminescence properties and energy transfer from Bi 3+ to Eu 3+ in CaWO4 :Eu 3+ /Bi 3+ nanophosphors were also investigated. The results revealed that red luminescence of CaWO4 :2Eu 3+ /1Bi 3+ nanophosphor is 5.4 times stronger than CaWO4 :2Eu 3+ . It was observed that the forces exist between Bi 3+ and Eu 3+ are due to the interaction of electric dipole-dipole interactions. The chroma of CaWO4 :2Eu 3+ /1Bi 3+ nanophosphors was calculated to be 97.40%. The energy transfer process was studied by measuring the decay curves due to Bi 3+ and Eu 3+ dopants. Enhanced red emission, high thermal stability, stronger 5 D0 → 7 F2 absorption intensity, high colour purity and decay studies indicate that CaWO4 :Eu 3+ /Bi 3+ nanophosphors are potential candidates to be used in white light-emitting diode ( w LEDs).